Challenges of Online Learning in the Post Covid-19 Era: Lived Experiences of Teachers in Remote Nepal - Gharti, Luk (English Language Teaching Perspectives, 2023)
This study examines Basic Level (6-8) and Secondary Level (9-10) teachers' experiences about online learning and its position after Covid-19 in the remote areas. To fulfil the objectives of the study, the researcher used semi-structured mediated and face-to-face interview with the teachers. The findings of this study showed that online learning in the remote areas is less effective and practical. The teachers were less motivated and higher preferences to face-to-face mode of teaching rather than online learning due to insufficient infrastructure of Information and Communication Technology (ICT), lack of basic knowledge and skill about ICT, unstable and no electricity and internet access. It found less feasible to receive equitable education and found gap between rich and poor students through online learning. Thus, the strategies of online learning seemed reluctant and beyond teachers' hand due to the lack of online learning tools with students, parents' financial condition, parents' guidance and awareness and lack of administration support. Overall, after Covid-19, online learning was found to be unused and uncertain about its progress in the future.